BK polyomavirus-associated nephropathy - Yo Han Ahn; Hee Gyung Kang (Childhood Kidney Diseases, 2022)
BK polyomavirus (BKPyV) is a ubiquitous virus residing in the kidney tubules and is clinically significant only in immunocompromised patients. In clinical practice, BKPyV is a causative pathogen of BKPyV-associated nephropathy (BKVAN) in kidney allograft recipients or hemorrhagic cystitis of hematopoietic stem cell transplant recipients. Currently, there is no effective treatment for BKVAN; therefore, careful monitoring and prudent modification of immunosuppression are necessary to prevent BKVAN. In this article, the epidemiology, pathophysiology, and current management strategies for BKVAN are reviewed.